Being on the Frontline? Immigrant Workers in Europe and the COVID-19 Pandemic - Francesco Fasani; Jacopo Mazza (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
We provide a first timely assessment of the pandemic crisis impact on the labour market prospects of immigrant workers in Europe by proposing a novel measure of their exposure to employment risk. We characterize migrants' occupations along four dimensions related to the role of workers' occupations in the response to the pandemic, the contractual protection they enjoy, the possibility of performing their job from home and the resilience of the industry in which they are employed. We show that our measure of employment risk closely predicts actual employment losses observed in European countries after the first wave of the COVID-19 pandemic. We estimate that, within industries and occupations, Extra-EU migrants and women are exposed to higher risk of unemployment than native men and that women are losing jobs at higher rates than equally exposed men. According to our estimates, more than 9 million immigrants in the EU14+UK area are exposed to a high risk of becoming unemployed due to the pandemic crisis, 1.3 million of which are facing a very high risk.
Keywords: F22; J61; J20; 330; employment risk; COVID-19; key occupations